2020
DOI: 10.5713/ajas.19.0173
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a promotes apoptosis of porcine granulosa cells by targeting the 3β-hydroxysteroid-Δ24-reductase gene

Abstract: Objective: Apoptosis of ovarian granulosa cells (GCs) affects mammalian follicular development and fecundity. This study aimed to explore the regulatory relationship between microRNA-26a (miR-26a) and the 3β-hydroxysteroid-Δ24-reductase gene (<i>DHCR24</i>) gene in porcine follicular granular cells (pGCs), and to provide empirical data for the development of methods to improve the reproductive capacity of pigs.Methods: The pGCs were transfected with miR-26a mimic, miR-26a inhibitor and <i>DHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…After 72 h of reperfusion, the mice were euthanized for analysis. The dose of oe-KLF2 vector was 100 nM, and n = 8 for mice in each group [47]. *, p < 0.05, vs. EVs-inhibitor NC or oe-NC or EVs-inhibitor NC + oe-NC in mouse brain tissue slices, #, p < 0.05, vs. EVs-miR-26a inhibitor + oe-NC in mouse brain tissue slices.…”
Section: Discussionmentioning
confidence: 99%
“…After 72 h of reperfusion, the mice were euthanized for analysis. The dose of oe-KLF2 vector was 100 nM, and n = 8 for mice in each group [47]. *, p < 0.05, vs. EVs-inhibitor NC or oe-NC or EVs-inhibitor NC + oe-NC in mouse brain tissue slices, #, p < 0.05, vs. EVs-miR-26a inhibitor + oe-NC in mouse brain tissue slices.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh porcine ovaries were obtained from a commercial slaughterhouse and transported back to the laboratory within 1 hr. Porcine ovarian granulosa cells (pGCs) were collected from porcine ovarian follicles (3–6 mm diameter) (Zhang et al, ), washed and centrifuged (1,000 g , 5 min), and then inoculated in a 6‐cm dish at a density of 1 × 10 6 cells. Cells were cultured in DMEM and Nutrient Mixture F‐12 medium (DMEM/F‐12), containing 10% FBS, 100 units/mL penicillin and 100 mg/ml streptomycin at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, SRSF1 function and its regulatory mechanism are rarely studied in reproduction, especially during GC apoptosis and follicular atresia. Interestingly, our previous RNAseq study highlighted a higher expression of SRSF1 in HFs than AFs, which hinted at its regulatory potential in GC apoptosis [4].…”
Section: Introductionmentioning
confidence: 93%
“…As a major component of the follicle, granulosa cells (GCs) function by closely interacting with the oocyte and theca cells and producing paracrine substances. Research has demonstrated that GCs' proliferation and function are essential in follicle development and maturation, while the GC apoptosis rate increases significantly with the progression of follicular atresia [4].…”
Section: Introductionmentioning
confidence: 99%